Transforming Health Care Through Meaningful Doctor of Nursing Practice Community Partnerships. Issue 3 (May 2019) - Hooshmand, Mary; Foronda, Cynthia; Snowden, Kenya; de Tantillo, Lila; Williams, Jessica Roberts
Abstract : Background: A critical component of doctor of nursing practice (DNP) education is practice immersion. DNP programs require 1000 hours of clinical practice experience to obtain the DNP degree. Problem: Faculty struggle with providing meaningful clinical experiences congruent with the role of the DNP. Approach: This article describes a unique practice immersion course joining DNP students with community health care partners to provide meaningful experiences with the potential to transform health care. DNP students are assigned system-level projects designed to create organizational change. Outcomes: Over the course of 4 years, the practice immersion opportunities more than doubled from 30 to 66 live projects. Integrating collaborative practice immersion into the curriculum builds students' leadership skills and strengthens long-standing bonds among academia, practice, and the community. Conclusions: The creation of structured, meaningful collaborations between DNP students and community partners is an approach that has the potential to facilitate transformative, sustainable change in health care. Abstract : Supplemental digital content is available in the text.